Effect of fat-reformulated dairy food consumption on postprandial flow-mediated dilatation and cardiometabolic risk biomarkers compared with conventional dairy: a randomized controlled trial. Issue 3 (10th January 2022) - Markey, Oonagh; Vasilopoulou, Dafni; Kliem, Kirsty E; Fagan, Colette C; Grandison, Alistair S; Sutton, Rachel; Humphries, David J; Todd, Susan; Jackson, Kim G; Givens, David I; Lovegrove, Julie A
ABSTRACT: Background: Longer-term consumption of SFA-reduced, MUFA-enriched dairy products has been reported to improve fasting flow-mediated dilatation (FMD). Yet, their impact on endothelial function in the postprandial state warrants investigation. Objectives: The aim was to compare the impact of a fatty acid (FA) modified with a conventional (control) dairy diet on the postprandial %FMD (primary outcome) and systemic cardiometabolic responses to representative meals, and retrospectively explore whether treatment effects differ by apolipoprotein E ( APOE ) or endothelial NO synthase ( eNOS ) Glu298Asp gene polymorphisms. Methods: In a crossover-design randomized controlled study, 52 adults with moderate cardiovascular disease risk consumed dairy products [38% of total energy intake (%TE) from fat: FA-modified (target: 16%TE SFAs; 14%TE MUFAs) or control (19%TE SFAs; 11%TE MUFAs)] for 12 wk, separated by an 8-wk washout. Blood sampling and FMD measurements (0–480 min) were performed pre- and postintervention after sequential mixed meals that were representative of the assigned dairy diets (0 min, ∼50 g fat; 330 min, ∼30 g fat). Results: Relative to preintervention (∆), the FA-modified dairy diet and meals (treatment) attenuated the increase in the incremental AUC (iAUC), but not AUC, for the %FMD response observed with the conventional treatment (–135 ± 69% vs. +199 ± 82% × min; P = 0.005). The ∆ iAUC, but not AUC, for the apoB response decreased after the FA-modified treatment yet increased after the conventional treatment (–4 ± 3 vs. +3 ± 3 mg/mL × min; P = 0.004). The ∆ iAUC decreased for plasma total SFAs ( P = 0.003) and trans 18:1 ( P < 0.0001) and increased for cis -MUFAs ( P < 0.0001) following the conventional relative to the FA-modified treatment. No treatment × APOE or eNOS genotype interactions were evident for any outcome. Conclusions: This study provides novel insights into the longer-term effects of FA-modified dairy food consumption on postprandial cardiometabolic responses.